An immunodominant DQ8 restricted gliadin peptide activates small intestinal immune response in in vitro cultured mucosa from HLA-DQ8 positive but not HLA-DQ8 negative coeliac patients. Issue 1 (1st January 2003) - Mazzarella, G; Maglio, M; Paparo, F; Nardone, G; Stefanile, R; Greco, L; van de Wal, Y; Kooy, Y; Koning, F; Auricchio, S; Troncone, R
Abstract : Background: Studies on intestinal T cell clones from the mucosa of patients with coeliac disease have led to the identification of immunogenic gliadin epitopes. One is HLA-DQ8 restricted, its recognition by T cells being increased by introduction of negatively charged residues operated by tissue transglutaminase. Aim: To test HLA-DQ8 restricted epitope in both native (QYPSGQGSFQPSQQNPQA) and deamidated (QYPSGEGSFQPSQENPQA) forms in an organ culture system of treated coeliac mucosa from HLA-DQ8 positive and HLA-DQ8 negative patients. Patients and methods: Jejunal biopsies obtained from 10 patients with coeliac disease (six HLA-DQ8 positive and four HLA-DQ8 negative) were cultured in vitro with a peptic-tryptic digest (PT) of gliadin, or with the native (peptide A) or deamidated (peptide B) peptide. Intraepithelial CD3 + and lamina propria total CD25 + and CD3 + CD25 + cells were counted, lamina propria intercellular adhesion molecule 1 (ICAM-1) expression was evaluated, as well as that of Fas molecules on epithelial cells. Results: In HLA-DQ8 positive, but not in HLA-DQ8 negative, coeliacs the density of intraepithelial CD3 + cells, lamina propria total CD25 +, and CD3 + CD25 + cells, as well as expression of ICAM-1 and Fas molecules were significantly increased in biopsies cultured with PT, peptide A, or peptide B compared with biopsies cultured in medium alone. Conclusion: These data show that the DQ8 restricted gliadin peptide is immunogenic only in the intestinal mucosa of HLA-DQ8 positive coeliac patients in both native and deamidated forms.